The preparation of cellulose nanocrystal/1, 3‐butylene glycol composite structural color films and humidity‐responsive. Issue 29 (25th May 2022) - Wang, Tianhui; Meng, Xiangnan; Lu, Shuyu; Ma, Tao; Hu, Xinna; Song, Yi
Abstract: Cellulose nanocrystals (CNCs) can self‐assemble in an aqueous solution to form a chiral nematic liquid crystal structure, which is maintained in the subsequent solid iridescent film and presents a unique structural color. In this study, in order to explore the effect of ultrasound on the optical properties of CNC, CNC films with a chiral nematic helix structure and different structural colors were prepared by ultrasonic‐assisted dispersion and natural static evaporation. Results showed that prolonging the ultrasonic duration significantly increased layer pitches and red‐shifted the color of CNC films, likely due to increased steric hindrance and a larger electric double layer. On this basis, CNC/1, 3‐butylene glycol (BG) composite films were prepared with uniform and structural color. Results showed that BG was incorporated into CNCs most likely through hydrogen bonds. Moreover, the presence of BG increased the layer pitches and red‐shifted the structural color of CNC/BG composite films, which indicates that structural color of the film has a good stability response to humidity. On the whole, our work provides a new point of view in understanding the role of ultrasound and small‐molecule additives in the preparation of CNC‐based films. Abstract : Utilizing the well‐established ultrasound assisted method, CNC/BG composite films with uniform and structural color were successfully prepared, 1, 3‐butylene glycol was found to incorporate into CNCs likely through hydrogen bonds, wrapping on the surface of CNCs. Moreover, the structural colors of the composite films achieve a fast and reversible humidity response from 35% to 80% at 25°C.